Cover Feature: Robust Acenaphthoimidazolylidene Palladacycles: Highly Efficient Catalysts for the Amination of N‐Heteroaryl Chlorides (Chem. Asian J. 18/2017). Issue 18 (4th September 2017) - Deng, Qinyue; Zhang, Yang; Zhu, Haibo; Tu, Tao
Abstract : The perfect match : Challenging and selective amination of N ‐ heteroaryl chlorides by diverse primary and secondary amines has been successfully realized by using robust and congested N‐heterocyclic carbene palladacycles as catalysts. Furthermore, the coupling protocol is readily extended to synthesize rosiglitazone, a clinical drug for diabetes mellitus, highlighting its potential pharmaceutical feasibility. More information can be found in the Communication by Tao Tu et al. onpage 2364 in Issue 18, 2017 (DOI:10.1002/asia.201700877 ).